Handbook of modern and contemporary Japanese women writers - Copeland, Rebecca L., 1956- (Amsterdam : Amsterdam University Press, 2023)
The Handbook of Modern and Contemporary Japanese Women Writers offers a comprehensive overview of women writers in Japan, from the late 19th century to the early 21st. Featuring 24 newly written contributions from scholars in the field-representing expertise from North America, Europe, Japan, and Australia-the Handbook introduces and analyzes works by modern and contemporary women writers that coalesce loosely around common themes, tropes, and genres. Putting writers from different generations in conversation with one another reveals the diverse ways they have responded to similar subjects. Whereas women writers may have shared concerns-the pressure to conform to gendered expectation, the tension between family responsibility and individual interests, the quest for self-affirmation-each writer invents her own approach. As readers will see, we have writers who turn to memoir and autobiography, while others prefer to imagine fabulous fictional worlds. Some engage with the literary classics-whether Japanese, Chinese, or European-and invest their works with rich intertextual allusions. Other writers grapple with colonialism, militarism, nationalism, and industrialization. This Handbook builds a foundation which invites readers to launch their own investigations into women's writing in Japan.
15. Beyond shōjo fantasy: women writers writing girlhood-Yoshiya Nobuko, Tanabe Seiko, and Hayashi Mariko / Hiromi Tsuchiya Dollase -- 16. Writing the aged woman: Enchi Fumiko and Tanabe Seiko / Sohyun Chun -- 17. Humor and aging: Ogino Anna, Itō Hiromi, and Kanai Mieko / Tomoko Aoyama -- Part 7: Colonies, war, aftermath -- 18. Women and war: Yosano Akiko and Hayashi Fumiko / Noriko J. Horiguchi -- 19. Women and colonies: Shanghai and Manchuria in the autobiographical writings of Hayashi Kyōko, Sawachi Hisae, and Miyao Tomiko / Lianying Shan.
Includes bibliographical references and index.
Description based on online resource; title from PDF title page (JSTOR, viewed on February 20, 2023).
JSTOR
Keywords: Japanese literature -- Women authors -- History and criticism; Literary studies: from c 1900 -; Gender studies: women; ART / Women Artists; LITERARY CRITICISM / Asian / Japanese; REFERENCE / Research; Japanese literature -- Women authors; Literary studies: general; Reference works; Gender studies: women and girls; Electronic books; Criticism, interpretation, etc